RAGAM BAHASA SLANG PADA KOMUNITAS PEKERJA SALON (KAJIAN SOSIOLINGUISTIK) - Rahmadiah Rahmadiah; Usman Usman; Hajrah Hajrah (Fakultas Bahasa dan Sastra Indoensia, 2023)
The aim of this research is to describe the forms of use of various slang languages in the salon worker community and to describe the function of the use of various slang languages in the salon worker community. This research uses descriptive and qualitative methods. Descriptive research takes the form of recording or other official records. Data collection techniques include observing, listening, interviews, and documentation techniques. The data analysis techniques used are data transcription, data grouping, data analysis, and drawing conclusions. The research results obtained focus on the form and function of the use of various slang languages in the salon worker community. The results of research on the variety of slang language in the salon worker community show ten data points on various forms of slang language, namely acronym slang form, metathesis slang form, abbreviation slang form, ephenthesis slang form, combination slang form